Mus81-Eme1-dependent aberrant processing of DNA replication intermediates in mitosis impairs genome integrity - Calzetta, Nicolás Luis (2020)
Chromosome instability (CIN) underpins cancer evolution and is associated with drug resistance and poor prognosis. Understanding the mechanistic basis of CIN is thus a priority. The structure-specific endonuclease Mus81-Eme1 is known to prevent CIN. Intriguingly, however, here we show that the aberrant processing of late replication intermediates by Mus81-Eme1 is a source of CIN. Upon depletion of checkpoint kinase 1 (Chk1), Mus81-Eme1 cleaves under-replicated DNA engaged in mitotic DNA synthesis, leading to chromosome segregation defects. Supplementing cells with nucleosides allows the completion of mitotic DNA synthesis, restraining Mus81-Eme1-dependent DNA damage in mitosis and the ensuing CIN. We found no correlation between CIN arising from nucleotide shortage in mitosis and cell death, which were selectively linked to DNA damage load in mitosis and S phase, respectively. Our findings imply the possibility of optimizing Chk1-directed therapies by inducing cell death while curtailing CIN, a common side effect of chemotherapy.